2015
DOI: 10.3892/etm.2015.2623
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary administration of anisodamine and nicorandil in individuals undergoing primary percutaneous coronary intervention for acute inferior myocardial infarction: A randomized factorial trial

Abstract: In acute inferior myocardial infarction (AIMI), numerous conventional drugs that are used to improve the myocardial microcirculation can significantly reduce blood pressure (BP) and coronary perfusion pressure, aggravate bradyarrhythmia and cause a deterioration in the hemodynamic state of the whole body, which greatly limits the application of these drugs in clinical settings. The aim of the present study was to assess the effect of anisodamine and nicorandil regimens on the prevention of no-reflow (NR) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…The mean age was 63.0 ± 10.0 years and 76.6% of the patients were male. All 10 studies were published in English [23][24][25][26][27][28][29][30][31] or Chinese [32]. Five studies had been conducted in Japan, four in China, and one in South Korea.…”
Section: Baseline Characteristics and Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…The mean age was 63.0 ± 10.0 years and 76.6% of the patients were male. All 10 studies were published in English [23][24][25][26][27][28][29][30][31] or Chinese [32]. Five studies had been conducted in Japan, four in China, and one in South Korea.…”
Section: Baseline Characteristics and Study Qualitymentioning
confidence: 99%
“…Three studies [24,26,27] failed to report follow-up, and in two studies [27,28], there was no incidence of NRP. Patients received nicorandil by intracoronary injection in five studies [23,24,29,31,32] and by intravenous injection in the others, with or without an oral dose later. We also recorded the time from onset of symptoms/STEMI to reperfusion.…”
Section: Baseline Characteristics and Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, in our analysis, cardiac tamponade and pericardial effusion were excluded events from in-hospital outcomes (Lee HC et al, 16 Chen C et al, Miyazawa A et al, Ono H et al and Ito H et al). 11,13,18,21 The data collected in studies showed that there is insufficient evidence at the moment on Nicorandil's ability to improve MACE. Of the thirteen RCTs performed with Nicorandil, only four of them used MACE as an endpoint (Lee HC et al, Chen C et al, Miyazawa A et al and Ono H et al).…”
Section: Discussionmentioning
confidence: 99%